Service quality in public and private hospitals in urban Bangladesh: a comparative study - Andaleeb, Syed Saad (© 2000 Elsevier Science Ireland Ltd., 2016)
This article was published in the Health Policy [© 2000 Elsevier Science Ireland Ltd.] and the definite version is available at: http://doi.org/10.1016/S0168-8510(00)00077-4 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S0168851000000774